2016
DOI: 10.1155/2016/3764681
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative Therapy of Type 1 Diabetes Mellitus: From Pancreatic Islet Transplantation to Mesenchymal Stem Cells

Abstract: Type 1 diabetes is an autoimmune disease resulting in the permanent destruction of pancreatic islets. Islet transplantation to portal vein provides an approach to compensate for loss of insulin producing cells. Clinical trials demonstrated that even partial islet graft function reduces severe hypoglycemic events in patients. However, therapeutic impact is restrained due to shortage of pancreas organ donors and instant inflammation occurring in the hepatic environment of the graft. We summarize on what is known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 205 publications
(240 reference statements)
0
16
0
Order By: Relevance
“…Although the high differentiation potential of embryonic stem cells and induced pluripotent stem cells surpasses that of MSCs, the latter have remained favorable for transplantation studies as MSCs are considered to be easily obtained from adult tissues, and exhibit immunodulatory and immunosuppressive properties, in addition to nontumorigenic differentiation potential ( 38 ). Therefore, MSCs have emerged as a better source for the generation of surrogate β cells ( 5 , 39 ). However, a number of studies have demonstrated that the hyperglycemic state in patients with diabetes may impair MSC function ( 40 , 41 ); the results of the present study indicated that cellular senescence may be one of the causes of this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Although the high differentiation potential of embryonic stem cells and induced pluripotent stem cells surpasses that of MSCs, the latter have remained favorable for transplantation studies as MSCs are considered to be easily obtained from adult tissues, and exhibit immunodulatory and immunosuppressive properties, in addition to nontumorigenic differentiation potential ( 38 ). Therefore, MSCs have emerged as a better source for the generation of surrogate β cells ( 5 , 39 ). However, a number of studies have demonstrated that the hyperglycemic state in patients with diabetes may impair MSC function ( 40 , 41 ); the results of the present study indicated that cellular senescence may be one of the causes of this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies had shown that MSCs preferentially homed to the sites of tissue damages, where they enhanced wound healing, and involved in modulating the balance of in ammatory response [21]. To determine whether Wip1 −/− MSCs could migrate to the damage sides in pancreas, red uorescence stained Wip1 −/− MSCs and Wip1 +/+ MSCs were administrated into T1DM mice.…”
Section: Ifn-α Secreted By Wip1 −/− Mscs Aggravated In Ammatory Respomentioning
confidence: 99%
“…They have been shown to be safe for application in patients [22][23][24]. Furthermore, as enhancers of epigenetic signals, HDACi have been applied to modulate cell differentiation in vitro [25][26][27][28]. In this work, we examined the effects of LBH589 and class I-specific HDACi MS-275 and MGCD103 on gene transcription in human mesenchymal bone-marrow derived stem cells.…”
Section: Introductionmentioning
confidence: 99%